2019
DOI: 10.3390/cryst9120633
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Removal of Calcium, Magnesium, and Nickel in Desalination by Alcaligenes aquatilis via Biomineralization

Abstract: In desalination, a high level of calcium (Ca) and magnesium (Mg) ions in seawater can cause scale deposition on the reverse osmosis membranes and water treatment systems. This process can significantly affect the efficiency of desalination. In addition, heavy metals in seawater affect human health. Therefore, Alcaligenes aquatilis from seawater was used to remove Ca, Mg, and nickel (Ni) by microbial-induced carbonate precipitation (MICP). The purification system was then analyzed by ionic analysis and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The basic constituents of the cementation medium, in function of the precursor chemicals used, will depend upon the metabolic pathway by which MICP transpires. MICP may occur through a variety of metabolic pathways; including photosynthesis [7], ureolysis [8][9][10], the ammonification of amino acids [11], denitrification (microbially induced desaturation and precipitation) [12,13] and methane oxidation [14], in addition to sulphate reduction and iron reduction [15]. The ureolysis or urea hydrolysis is the most efficient process among all MICP methods, as it has the potential to produce a large amount of calcite (CaCO 3 ) within a short period of time [16], and hence is of particular interest for Engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…The basic constituents of the cementation medium, in function of the precursor chemicals used, will depend upon the metabolic pathway by which MICP transpires. MICP may occur through a variety of metabolic pathways; including photosynthesis [7], ureolysis [8][9][10], the ammonification of amino acids [11], denitrification (microbially induced desaturation and precipitation) [12,13] and methane oxidation [14], in addition to sulphate reduction and iron reduction [15]. The ureolysis or urea hydrolysis is the most efficient process among all MICP methods, as it has the potential to produce a large amount of calcite (CaCO 3 ) within a short period of time [16], and hence is of particular interest for Engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously discovered fungi [71,72], actinomycetes [73], yeast species [74], and bacteria [75][76][77], recent five-year studies have isolated and identified lots of new UPB (Table 2) [67,70,[78][79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: Microorganismsmentioning
confidence: 99%
“…By inducing the mineralization of soil containing Pb, Zn, and Cd, Pasteurella bioremediation is superior to chemical precipitation technology in terms of long-term stability [90,97]. Furthermore, MICP is used for metal ion mineralization in high-salt produced water or the seawater desalination process [80,135]. Avoid adding UPB bacteria to the soil, and domesticating UPB through in situ biological stimulation.…”
Section: Mixed Hmsmentioning
confidence: 99%
“…Many calcium sources are used in the cementation solution to induce microorganisms to produce precipitation, including calcium chloride, calcium acetate, calcium gluconate and calcium lactate [149]. In recent years, researchers have proposed substitutes for commonly-used calcium salts, such as eggshells, seawater, papermaking wastewater, which are more economical and environmentally friendly [150]. Røyne et al [151] proposed the use of limestone powder as the calcium source for MICP application.…”
Section: Sources Of Calciummentioning
confidence: 99%